Evaluation of Compensation Policies and Their Impact on Employee Retention in the Food Industry - Sari Fitri (PT Agung Media Publisher, 2024)
This research study explores the evaluation of compensation policies and their impact on employee retention in the food industry. Employee retention is a critical concern for businesses operating in this highly competitive sector. The study aims to understand the relationship between compensation policies and employee retention, providing insights into the strategies that can be implemented to attract and retain skilled employees. The research methodology involves a comprehensive analysis of existing literature, industry reports, and case studies to gather relevant data on compensation policies and their impact on employee retention in the food industry. The findings highlight the significant factors that influence employee retention and the effectiveness of compensation policies in addressing these factors. The study reveals that fair and competitive compensation packages play a vital role in attracting and retaining skilled employees in the food industry. When employees feel adequately rewarded for their contributions, they are more likely to stay with the organization. Regular market analysis and benchmarking are crucial to ensure that compensation policies remain competitive and aligned with industry standards. Performance-based incentives, such as bonuses and recognition programs, are found to have a positive impact on employee motivation and retention. By rewarding high-performing employees, organizations foster a culture of excellence and encourage continuous improvement. Additionally, offering comprehensive benefits and perks, including healthcare plans, flexible work arrangements, and professional development opportunities, is instrumental in enhancing job satisfaction and promoting employee retention.